The Representation of Patriarchy in Indonesian Children Folk Tales from Sumatra Island - Dewi, Dyani Masita (Lingua Cultura, 2019)
This research aimed to discuss the topic of patriarchal research because it still existed in several countries in the world,Â especially Asia and more specifically, in Indonesia. This research was conducted to reveal how patriarchal values wereÂ reflected in Indonesian childrenâ€™s folk tales from Sumatra Island. This research used a sociological approach to literatureÂ and used semiotic theory to analyze the data obtained. The researcher chose to use a qualitative descriptive method soÂ that the analysis process could be described completely. The main data used in this research are several childrenâ€™s folkÂ tales originating from Sumatra Island, namely Province of North Sumatra (â€œDi Balik Derita Si Boru Tombagaâ€, â€œBohongÂ Merinangâ€, and â€œSi Kodok Kata Malem, Baik Budi Penawan Hatiâ€), South Sumatra (â€œLangkuse dan Putri Rambut Putihâ€),Â and Jambi (â€œLegenda Bukit Perakâ€). This research finds that patriarchal values are represented in how women are associatedÂ with domestic works, women are considered as the subordinates and inferiors, as well as showing their dependence on men.